Lippincott manual of nursing practice. - Nettina, Sandra M. (Philadelphia : Lippincott Williams & Wilkins, 2010)
This classic reference book is the one source every nurse needs for essential nursing knowledge. Designed in an easy-to-read format, this guide covers a wide range of disorders and patient problems in all basic areas of nursing, including, medical-surgical, pediatric, maternity, and psychiatric.
Nursing practice and the nursing process -- Standards of care, ethical and legal issues -- Health promotion and preventive care -- Genetics and health applications -- Adult physical assessment -- I.V. therapy -- Perioperative nursing -- Cancer nursing -- Care of the older or disabled adult -- Respiratory function and therapy -- Respiratory disorders -- Cardiovascular function and therapy -- Cardiac disorders -- Vascular disorders -- Neurologic disorders -- Eye disorders -- Ear, nose, and throat disorders -- Gastrointestinal disorders -- Hepatic, biliary, and pancreatic disorders -- Nutritional problems -- Renal and urinary disorders -- Gynecologic disorders -- Breast conditions -- Endocrine disorders -- Diabetes mellitus -- Hematologic disorders -- Transfusion therapy and blood and marrow stem cell transplantation -- Asthma and allergy -- HIV disease and AIDS -- Connective tissue disorders -- Infectious diseases -- Musculoskeletal disorders -- Dermatologic disorders -- Burns -- Emergent conditions -- Maternal and fetal health -- Nursing management during labor and delivery -- Care of mother and neonate during the postpartum period -- Complications of the childbearing experience -- Pediatric growth and development -- Pediatric physical assessment -- Pediatric primary care -- Care of the sick or hospitalized child -- Pediatric respiratory disorders -- Pediatric cardiovascular disorders -- Pediatric neurologic disorders -- Pediatric eye and ear problems -- Pediatric gastrointestinal and nutritional disorders -- Pediatric renal and genitourinary disorders -- Pediatric metabolic and endocrine disorders -- Pediatric oncology -- Pediatric hematologic disorders -- Pediatric immunologic disorders -- Pediatric orthopedic problems -- Pediatric integumentary disorders -- Developmental disabilities -- Problems of mental health.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nursing -- Handbooks, manuals, etc; Nursing Care -- Handbooks; Electronic books